Evaluation of Expanded Clay and Tuff as Lightweight Agents in Concrete Stabilized with Nopal Mucilage and Aloe Vera - Daniel Mendoza-Goden; Rocio Rafaela Gallegos-Villela; Pedro Flores-Becerra; Josue Francisco Perez-Sanchez; Edgardo Jonathan Suarez-Dominguez; Arturo Palacio-Perez (Eng)
Objectives: This study aims to evaluate the potential of lightweight concrete mixtures incorporating sustainable materials, such as nopal mucilage and aloe vera, to enhance thermal and structural performance while promoting eco-friendly construction practices. The objective is to analyze their effects on physical, mechanical, and thermal properties to optimize mixture design. Methods/Analysis: Six lightweight concrete mixtures were prepared using varying dosages of tuff, expanded clay, nopal mucilage, and aloe vera as lightweight and stabilizing agents. To assess their performance, a series of physical tests (bulk density, water absorption, and slump), mechanical tests (compressive strength), and thermal characterizations (conductivity, heat capacity, and resistivity) were conducted. Fractal analysis was employed to evaluate the structural complexity of the mixtures. Findings: The results revealed significant differences based on the materials used. Mixtures with aloe vera exhibited extreme water absorption (up to 11.472%) and varying consistency, from fluid (“spreads”) with tuff to workable with expanded clay. When combined with expanded clay, Nopal mucilage-based mixtures showed lower workability but higher compressive strengths (up to 11.447 MPa). Expanded clay increased bulk density and enhanced thermal efficiency, with mixtures incorporating aloe vera or nopal mucilage demonstrating high heat retention and structural complexity. The compressive strengths ranged from 7.343 MPa (aloe vera-tuff) to 12.207 MPa (water-tuff), highlighting the impact of stabilizing agents on mechanical performance. Novelty or Improvement: This study introduces a novel evaluation of lightweight concrete mixtures using nopal mucilage and aloe vera, focusing on their synergistic effects with lightweight aggregates such as tuff and expanded clay. The findings provide valuable insights into optimizing eco-friendly concrete mixtures with improved thermal retention, workability, and mechanical properties, offering a sustainable alternative for modern construction.